EFEKTIVITAS PELAKSANAAN LAYANAN INFORMASI DENGAN MEMANFAATKAN PRINSIP-PRINSIP HIGH TOUCH DALAM MENINGKATKAN MOTIVASI BELAJAR - ., Irmayanti; ., Daharnis; ., Marjohan (Konselor, 2013)
This research is purpose to know the effectiveness in improving â€œlayanan informasiâ€ about learning motivation of students. This research used experimental techniques that involving 80 students for group experimental and control group. This research resulted is a significant increase of motivation of learning of students before and after the experiment group given the treatment â€œlayanan informasiâ€ by utilizing the principles of high touch (posttest). Beside that, there are also differences in students learning motivation level control group before and after treatment in the form of â€œlayanan informasiâ€ provided without utilizing the principles of high touch. Increase the motivation of learning in the experimental group is given preferential treatment in the form of â€œlayanan informasiâ€ by utilizing the principles of high touch, that much higher when compared to the control group when its not given in the form of treatment the principles of high touch in â€œlayanan informasiâ€. The results of this research is recommended for the teacher/counselor at school that can improve the implementation of â€œlayanan informasiâ€ to increase the motivation of students in learning by utilizing the principles of high touch. Keyword:layanan informasi; high touch; motivation